2015
DOI: 10.1242/dmm.020859
|View full text |Cite
|
Sign up to set email alerts
|

Phospholamban overexpression in mice causes a centronuclear myopathy-like phenotype

Abstract: Centronuclear myopathy (CNM) is a congenital myopathy that is histopathologically characterized by centrally located nuclei, central aggregation of oxidative activity, and type I fiber predominance and hypotrophy. Here, we obtained commercially available mice overexpressing phospholamban (PlnOE), a well-known inhibitor of sarco(endo)plasmic reticulum Ca2+-ATPases (SERCAs), in their slow-twitch type I skeletal muscle fibers to determine the effects on SERCA function. As expected with a 6- to 7-fold overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(62 citation statements)
references
References 70 publications
6
55
1
Order By: Relevance
“…Furthermore, the type IIA fibers from Pln OE / Sln KO mice failed to undergo the typical compensatory hypertrophy observed in the Pln OE mice (Fig 3F and reference [3]), and the type IIX fibers showed a similar pattern (Fig 3F); however the one-way ANOVA did not indicate statistical significance ( p = 0.11). There was also a significant reduction in total fiber count in the Pln OE / Sln KO soleus muscles compared with both Pln OE and WT mice (Fig 4B).…”
Section: Resultsmentioning
confidence: 87%
“…Furthermore, the type IIA fibers from Pln OE / Sln KO mice failed to undergo the typical compensatory hypertrophy observed in the Pln OE mice (Fig 3F and reference [3]), and the type IIX fibers showed a similar pattern (Fig 3F); however the one-way ANOVA did not indicate statistical significance ( p = 0.11). There was also a significant reduction in total fiber count in the Pln OE / Sln KO soleus muscles compared with both Pln OE and WT mice (Fig 4B).…”
Section: Resultsmentioning
confidence: 87%
“…We have recently reported that the Pln OE mouse histopathologically resembles human autosomal dominant CNM (Fajardo et al. ), which, in contrast to myotubular myopathy, is generally less severe, and patients often have a normal lifespan with very few respiratory complications (Bitoun et al. ; Jungbluth et al.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis was performed to determine expression levels of SERCAs, SLN, PLN, and dynamin 2 in the diaphragm muscles from WT and Pln OE mice as previously described (Fajardo et al. ). In addition, calcineurin expression and NFAT nuclear localization in soleus, gluteus minimus, and diaphragm muscles were assessed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SLN expression is also developmentally regulated in rodents; it is relatively high in fetal and neonatal skeletal muscles but gradually becomes restricted to slow-twitch oxidative muscle fibers in adult rodents [34]. The expression of SLN is independently regulated from SERCA and can be affected by disease states [35, 36]. The expression of SLN varies in small and large mammals.…”
Section: Sarcoplasmic Reticulum Is a Critical Player In Muscle Physiomentioning
confidence: 99%